The Effect of Selected Combined Training on Strength,Balance and Life Quality of Multiple Sclerosis Patients - M.R Kordi; lila Anousheh; sara Khodadadeh; niko Khosravi; bahram Sanglaji (Sport Sciences and Health Research)
The aim of this study was to investigate the effect of selected combined training on strength, balance and quality of life in patients with multiple sclerosis. 45 patients from Iran MS Association were voluntarily selected as the statistical population. 38 volunteers participated in this study and randomly divided into control (mean+SD: age 31.631+6.001 yrs, weight 62.684+12.194 kg, height 165.115+7.587cm) (n=19) and experimental (mean+SD: age 32.500+6.031 yrs, weight 64.527+9.915 kg, height 165.055+8.557cm) (n = 19). Experimental group performed a progressive combined exercise including stretching, aerobic exercises, resistance and balance training for 24 sessions during 8 weeks. The control group did not perform any training. Strength, balance and quality of life were measured by one repetition maximum (1RM), Berg Balance Scores (BBS) and Multiple Sclerosis Quality of Life – 54 questionnaire (MSQOL – 54) respectively one week before and after the training (P=0.05). t test results showed that strength and balance increased significantly after the training program in the experimental group (P< 0.05). Also, eight weeks of combined training improved quality of life, but this improvement was not significant (P>0.05). It is suggest that combined training can be beneficial to MS patients.